Psoriasis and porphyria cutanea tarda, associated with chronic hepatitis C in HIV-infected patients (clinical observation) - I. A. Korotaeva; L. F. Sklyar; A. I. Simakova; L. G. Singur; A. F. Popov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The continued growth of HIV-infected patients is associated on the one hand, with increase of life expectancy because of antiretroviral therapy, and the other - with high incidence of new cases of HIV-infection. It is important to remember that almost every HIV-infected patient has concomitant disease. The presence of comorbidity increases days of hospitalization, disability, impedes rehabilitation and leads to polypharmacy. Moreover, polypharmacy, particularly in HIV-patients, contributes to a sharp increase of adverse local and systemic side effects of drugs. This article presents the clinical examples of skin diseases in patients with HIV-infection.